2015
DOI: 10.1155/2015/969580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on Microstructure and Mechanical Properties of Magnetron Sputtered Cu Thin Films

Abstract: Cu thin films were deposited on Si substrates using direct current (DC) magnetron sputtering. Microstructure evolution and mechanical properties of Cu thin films with different annealing temperatures were investigated by atomic force microscopy (AFM), X-ray diffraction (XRD), and nanoindentation. The surface morphology, roughness, and grain size of the Cu films were characterized by AFM. The minimization of energy including surface energy, interface energy, and strain energy (elastic strain energy and plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Then, the internal stress distribution could be more even which could make the (220) grain with minimization strain energy grown easily and quickly. Du et al [33] noticed a change in preferred orientation after annealing from (111) to (220). They explained this phenomenon by the effect of yield in (220) grain starting before the (111) grains.…”
Section: Film Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the internal stress distribution could be more even which could make the (220) grain with minimization strain energy grown easily and quickly. Du et al [33] noticed a change in preferred orientation after annealing from (111) to (220). They explained this phenomenon by the effect of yield in (220) grain starting before the (111) grains.…”
Section: Film Strainmentioning
confidence: 99%
“…Quantification of the surface roughness (average surface roughness Ra and total height of the roughness profile Rt) for both samples is presented in Table 3. It is well known for sputtering techniques that substrate temperature plays a key role in controlling the film growth process, leading to modification in surface smoothness [33][34][35] and change in film structure, specifically grain growth. Chan et al [36] demonstrated an increase of the root mean square roughness Rq and lateral feature size of films of 500 nm thick films when the substrate temperature varied from 25 to 250 °C.…”
Section: Surface Morphology and Microstructurementioning
confidence: 99%
“…Due to the increased surface energy during annealing, particles fuse resulting in increased aggregate formation. This fusion process of the particles also causes the growth of a few grains which increases poly-dispersity [25][26][27]. Size analysis of the annealed particles shows the size range between 10 nm and 45 nm.…”
Section: Field Emission Gun Scanning Electron Microscopymentioning
confidence: 99%
“…2 with the calculated values summarized in Table 1. However, reports have shown that annealing the copper substrate at high temperature changes its crystal structure [38]. It was shown that at a temperature of up to 350°C, Cu (111) is dominant, and upon increasing the temperature to 500°C, the structure begins to change to Cu (100) [39].…”
Section: Crystallinity and Morphology Of The Substrates Crystallinitymentioning
confidence: 99%